2020
DOI: 10.1002/ijc.32856
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype molding of T cells in colorectal cancer by single‐cell analysis

Abstract: The majority of patients with microsatellite stable (MSS) colorectal cancer (CRC) do not benefit from the immunotherapies directed at rescuing T‐cell functions. Therefore, complete understanding of T‐cell phenotypes and functional status in the CRC microenvironment is desirable. Here, we applied single‐cell mass cytometry to mold the T‐cell phenotype in 18 patients with MSS CRC for better understanding of CRC as a systemic disease and to search for tumor‐driven T‐cell profile changes. We show interpatient and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…The enrichment of ICOS, CD45RO, PD-1, programmed death-ligand 1 (PD-L1), lymphocyte-activation gene 3 (LAG-3), CTLA-4, and T-cell immunoglobulin mucin-3 (TIM-3) on BLIMP-1 + regulatory T cells suggested that BLIMP-1 + Treg cells have a more activated phenotype than conventional Treg cells and may play a role in the antitumor immune response. Di et al [ 41 ] also found that exhausted T cells (PD-1 + CD38 + HLA-DR + CCR7 + CD127 – ) and regulatory T cells (CD4 + CD25 + CD127 – ) were increased in tumor tissues. Moreover, they found that CD8 + CD28 – immunosenescent T cells with impaired proliferation capacity were the most abundant T cell population in colorectal tumors.…”
Section: Immune Landscape Of Colorectal Cancersmentioning
confidence: 99%
“…The enrichment of ICOS, CD45RO, PD-1, programmed death-ligand 1 (PD-L1), lymphocyte-activation gene 3 (LAG-3), CTLA-4, and T-cell immunoglobulin mucin-3 (TIM-3) on BLIMP-1 + regulatory T cells suggested that BLIMP-1 + Treg cells have a more activated phenotype than conventional Treg cells and may play a role in the antitumor immune response. Di et al [ 41 ] also found that exhausted T cells (PD-1 + CD38 + HLA-DR + CCR7 + CD127 – ) and regulatory T cells (CD4 + CD25 + CD127 – ) were increased in tumor tissues. Moreover, they found that CD8 + CD28 – immunosenescent T cells with impaired proliferation capacity were the most abundant T cell population in colorectal tumors.…”
Section: Immune Landscape Of Colorectal Cancersmentioning
confidence: 99%
“…Moreover, it has been shown that patients with microsatellite stable (MSS) cancers do not benefit from immunotherapy as microsatellite instable (MSI) cancers (Emambux et al, 2018). In fact, in a recent study, it was shown that the dynamics of the T-cells phenotype differ between MSS and MSI cancers (Di et al, 2020). Future studies should be conducted to correlate the status of microsatellite stability with the functional effects of EVs.…”
Section: Resultsmentioning
confidence: 99%
“…Due to a lack of robust effector functions, exhausted T cells express multiple inhibitory receptors with an altered transcriptional programme ( 25 ). An abundance of exhausted T cells results in an invalid control of tumors, leading to poor prognosis ( 26 29 ). Yet, after deconvolution of the TCGA HCC RNA-seq data with CIBERSORTx, the proportion distribution of 11 cell types (mainly six cell types) in tumor and normal tissues showed a different trend.…”
Section: Discussionmentioning
confidence: 99%